STATE’S AUTHORITY RIGHTS OVER LAND IN INDONESIA - Awaluddin, Awaluddin (Tadulako Law Review, 2017)
The basic principle mentioned about the right over land by state is very basic according Article 33 Paragraph (3) of the 1945 Constitution which states "" earth and air and natural resources contained within it controlled by the state and used for the stock of people's prosperity." This research is intended to seek and understand whether the meaning of rights by the state can be interpreted also as the right of the state (eigenaar) to the land in Indonesia. This research uses research methods with the approach of legislation and conceptual road. Based materials from books law and research journals are the main legal ingredients. The results show that state copyright is interpreted as a state authority, judicial, air and space rules and regulations.